Contested governance: police and gang interactions - Kinnes, Irvin (Institute of Criminology, 2017)
Gangs in Cape Town have long been associated with high levels of violence and police efforts on the Cape Flats, while state agencies have not yet been able to bring any significant relief to the affected communities or growing gang structures. It seems the conventional approaches need reconceptualization. This thesis explores a nodal governance approach to the forms and consequences associated with the policing of gangs by police. Developments in governance theory has brought new insights for our understanding of how state and non-state actors relate in and across different networks, and especially within the security governance networks. However, such research has failed to consider how gangs and police interact and regulate each other through their own governance and conflict with one another. In attempts by the police to govern gangs (and by extension the community), a state of contested governance arises between gangs and police nodes of power. This thesis argues that contrary to previous understandings, the organised gangs of Cape Town regulate and impact the way the police police gangs, which in turn affects the way gangs police themselves, and goes on to explore these interactions.